THE ROLES OF PERSON DEIXIS IN HALIMAH YACOB’S SPEECHES - PUSPITASARI, DINDA (LANGUAGE HORIZON, 2018)
Person deixis is a type of deixis that exemplified the encoding of participants? role in the speech event where the utterance in question is given. In other words, the expression of person deixis is described as referring to the person who the speaker intends to refer. In political speech, person deixis plays a very important role. It can be used to represent the speaker?s identity through his way the speaker refers to himself, his opponent, and his audience. In this study, the writer examines person deixis used by the Eighth President of Singapore, Halimah Yacob in her speeches. This study aims to find out the type of person deixis and to explain the roles of personal pronoun (I, we, you, they) used by Halimah Yacob in her speeches. This study uses a qualitative method, documentation technique in collecting data. The result shows the types of person deixis that are first person, second person, and third person deixis appeared in Halimah?s speeches. The most types of person deixis that used by Halimah Yacob is first person deixis. Another, there are some roles of personal pronoun (I, you, we, they) that used by Halimah Yacob. The most personal pronouns in three speeches used by Halimah Yacob is I then following by pronoun we. Halimah becomes a president is not only there is no candidate who passed a Certificate of Eligibility but she wants to show her positive qualities through her personal experiences before becoming a president by using the pronoun I. She also wants to show her commitment seriously to solves the problems that existed in Singapore by using the pronoun I. However, Halimah used the pronoun I to refers herself rather than used pronoun we as represents herself and her administrations. Halimah becomes the only one to be blamed if there is something happen. Even though Halimah used the pronoun I which is distancing herself with her administrations but she still can get responsibility from the audiences. In this case, the second place is the use of personal pronoun we which is referred to Halimah and the audiences. Halimah used the personal pronoun we is to shares responsibility and creates involvement with the audiences. So, Halimah used mostly first person deixis (I and we) above to manipulate the use of pronouns which is to create good effects on the audience, such as highlighting her achievements, shortening the distance from the audience, denying or distancing themselves from the responsibility for specific political action, and encouraging solidarity